Exosome markers of LRRK2 kinase inhibition - Wang, Shijie (NPJ Parkinsons Dis, 2020)
Hyper-activated LRRK2 is linked to Parkinson’s disease susceptibility and progression. Quantitative measures of LRRK2 inhibition, especially in the brain, maybe critical in the development of successful LRRK2-targeting therapeutics. In this study, two different brain-penetrant and selective LRRK2 small-molecule kinase inhibitors (PFE-360 and MLi2) were orally administered to groups of cynomolgus macaques. Proposed pharmacodynamic markers in exosomes from urine and cerebrospinal fluid (CSF) were compared to established markers in peripheral blood mononuclear cells (PBMCs). LRRK2 kinase inhibition led to reductions in exosome-LRRK2 protein and the LRRK2-substrate pT73-Rab10 in urine, as well as reduced exosome-LRRK2 and autophosphorylated pS1292-LRRK2 protein in CSF. We propose orthogonal markers for LRRK2 inhibition in urine and CSF can be used in combination with blood markers to non-invasively monitor the potency of LRRK2-targeting therapeutics.